Avaliação de um sistema de irrigação por aspersão do tipo pivô central móvel - Lima, Adenilsom dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
Um sistema de irrigação deve possibilitar o manejo eficiente da lâmina de água aplicada. Para tal, é necessário avaliar o desempenho do sistema em operação. Este trabalho teve por objetivo avaliar a uniformidade de distribuição de água em um sistema de irrigação por aspersão do tipo pivô central rebocável operando em duas áreas com condições de desníveis e comprimento de adutora distintas. O ensaio foi realizado na fazenda Buriti Mirim, no município de Angatuba – SP, com duas regulagens no relê percentual, a 15% e 100%, com os pluviômetros espaçados de três em três metros, colocados em média a 0,50m de altura em relação ao solo. Para a avaliação do desempenho do sistema, utilizou-se o coeficiente de uniformidade de Christiansen (CUC) e o coeficiente de uniformidade de distribuição (CUD), baseados a partir das lâminas de água coletadas em pluviômetros instalados sob os emissores do equipamento. Verificou-se que todos os valores do CUC ficaram abaixo dos valores mínimos recomendados demonstrando baixa eficiência na distribuição de água do equipamento, e que as mudanças de posição afetaram os valores de lâmina d’água aplicados em relação aos valores de projeto.

An irrigation system must possibilities the handling of the water with the maximum efficacy. For such, is necessary to evaluate the performance of the system in operation. Some parameters are used in the evaluations, the most important are: the uniformity of water distribution (CUD), and the Christiansen uniformity coefficient (CUC). So, the study had for objective to evaluate the uniformity of water distribution sprinkler system of central pivot removable that operates in three different areas, in different levels and distinct length of main line, comparing and quantifying the values of uniformity and water table average applied in two positions of operation of the equipment, as well as the operational conditions of the system in function of these changes. The study was carried through at Buriti-Mirim farm, in Angantuba - SP, with two regulations in rereads percentage, 15% and 100%, with the rain gauges spaced three meters each, distributed 0,50m average above soil surface. For the evaluation of the performance of the system, the Christiansen uniformity coefficient was used (CUC), based from the water table collected in rain gauges installed under the equipment sprinklers. It was verified that all the values for the uniformity coefficients had been below of the recommended minimum values demonstrating low efficiency in the water distribution of the equipment, and that the position changes had affected the values water table applied in relation to the values of project.
Keywords: Irrigação - Manejo; Equipamento agricola; Irrigação - Qualidade; Uniformity coefficient